Determination of the Real Influence of the Addition of Four Thickening Agents in Creams Using Rheological Measurements - Isaac, Vera Lucia Borges [UNESP]; Moraes, Jemima D. D. [UNESP]; Chiari, Bruna G. [UNESP]; Guglielmi, Danila A. S. [UNESP]; Cefali, Letícia C. [UNESP]; Rissi, Nathália C. [UNESP]; Correa, Marcos Antonio [UNESP] (Taylor & Francis, 2013)
This study aimed to characterize different emulsions obtained by the addition of four thickening agents, using rheological measurements, beyond analyzing the emulsions by polarized light microscopy looking for liquid crystals on them. The addition of these four thickening agents did not modify the base emulsion rheology, only an improvement in the sensory of the formulation was verified. The polarized light microscopy showed the formation of liquid crystalline structures in all the formulations, thus, the thickening agents did not influence in this parameter too. However, the emulsions could be considered appropriated for cosmetic purposes, probably being highly physically stable. © 2013 Copyright Taylor and Francis Group, LLC.
Keywords: Emulsions; liquid crystals; polymers; rheology; thickening agents; Emulsion rheology; Liquid crystalline; Rheological measurements; Thickening agents; Elasticity; Emulsification; Liquid crystals; Polymers; Rheology